Toxicity and Developmental Disruption of Piper aduncum Nanoemulsion against Paracoccus marginatus under Laboratory Conditions - Mega Andini; Eka Candra Lina; Novri Nelly (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2025)
Paracoccus marginatus is one of the important pests that can reduce papaya production. Piper aduncum nanoemulsion has potential as a botanical pesticide to control papaya mealybug (Paracoccus marginatus). This present research was aimed to determine the most effective concentration in suppressing the development of P. marginatus. This study consisted of 6 treatments and 5 replications: 0.33%, 0.43%, 0.57%, 0.75%, 0.99%, and control. The observed parameters were: nymph mortality, adult mortality, daily mortality, adult emergence, LC50, and LC95. The data obtained were analyzed using variance (ANOVA) and 5% Tukey. The LC50, and LC95 value was analyzed using Polo Plus. Piper aduncum nanoemulsion exhibits strong insecticidal activity against nymphs and adults of Paracoccus marginatus under laboratory conditions. Among the concentrations tested, 0.99% was the most effective, causing 81.11% nymph mortality at 72 hours post-application; adult emergence was limited to only 13.33%. The LC₅₀ and LC₉₅ values at 72 hours were 0.506% and 1.222%, reflecting the potency of the nanoemulsion at relatively low doses. Further research under field conditions is recommended to evaluate its efficacy, formulation stability, and safety on non-target organisms.